Star fruit juice business development strategy planning using the SWOT method and Fuzzy Analytical Hierarchy Process (FAHP) (Case Study of CV Angkasa Jaya, Blitar City) - Miftakhurrizal Kurniawan; Imam Santoso; Harry Mangatur Silaban (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2019)
The purpose of this study is to analyze the internal and external factors that influence development and provide proposals for competitive strategies which are the priority of developing CV Angkasa Jaya. This study uses Strength, Waekness, Opportunity and Threat (SWOT) methods to identify internal and external factors of the company as well as alternative strategic planning and Fuzzy Analytical Hierarchy Process (FAHP) for determining strategic priorities. The results showed that internal and external factors that affected were products, marketing, production processes, the existence of government support, fruit beverage trends, market potential, technology, competition, shifting market tastes, economy and substitute products. Alternative strategies that become priority development strategies that can be applied by CV Angkasa Jaya are to increase the use of production technology and the internet, improve and maintain product quality in order to be able to compete with other products, develop business potential by making product innovations, carry out continuous production processes, improve and maintain market share, increase production capacity and the last priority is to increase promotion.